Tectorigenin inhibits osteosarcoma cell migration through downregulation of matrix metalloproteinases in vitro - Guo, Yu (Anticancer Drugs, 2016)
Tectorigenin (Tec) is an effective component of the traditional Chinese medicine Belamcanda chinensis, which has been reported to exert beneficial effects in various types of cancer. However, the activity and mechanism of Tec in osteosarcoma (OS) have not been investigated to date. The aim of the present study was to examine the inhibitory effect of Tec on OS and its underlying mechanism of action. OS cells (Saos2 and U2OS) were treated with various concentrations of Tec for 24, 48, and 72 h. Cell proliferation was evaluated using an CCK-8 assay. Cell migration and invasion ability were measured using the Transwell assay. The expressions of MMP1, MMP2, MMP9, and cleaved caspase3 were measured using real-time PCR and/or western blot analysis. We found that Tec inhibited the proliferation of OS cells (Saos2 and U2OS) in a dose-dependent and time-dependent manner. In addition, Tec significantly inhibited migration and invasion in OS cells (P<0.05). Tec upregulated the expression of cleaved caspase3, while downregulating the expression of MMP1, MMP2, and MMP9. Taken together, the present study provided fundamental evidence for the application of Tec in chemotherapy against OS.